Strategies of optimalization of human resources performance in PT Rekadaya Elektrika - Fachruddin, Achmad; Rifin, Amzul; Asnawi, Yudha Heryawan (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to analyze internal and external factors that influence the improvement of optimization of company performance, analyze the performance of human resources at PT Rekadaya Elektrika, and formulate alternative strategies of PT rekadaya elektrika in the face of high market competition seen from SDM performance. This research method uses quantitative with the number of respondents as much as 5 out of 3 from the internal and 2 from the external. Data analysis techniques using IFE, EFE, SWOT and QSP Matrix Analysis. Data analysis results on IFE marks weigh 2,722, while on EFE matrix weighs 2,924. Research results show that IE Matrix is in the quarter 5 that is growth and stable. Whereas the alternative strategy that is the first priority of the QSP Matrix results is social protection and employee welfare (remuneration) with an attractive score value of 6,033. The results of the descriptive analysis on the HR Score Card explain that the competency development perspective is the focus of the company to the vision of the mission of the enterprise. The managerial implications of this study can provide increased productivity, improved employee retention and optimized SDM with employee protection and welfare strategies.